1981
DOI: 10.1042/bj2000501
|View full text |Cite
|
Sign up to set email alerts
|

The dependence on Ca2+ of phosphatidylinositol breakdown and enzyme secretion in rabbit neutrophils stimulated by formylmethionyl-leucylphenylalanine or ionomycin

Abstract: 1. We have measured the breakdown of [3H]phosphatidylinositol in rabbit neutrophils prelabelled with [3H]glycerol by a pulse-chase procedure. With a view to defining a possible causal relationship between phosphatidylinositol breakdown and enzyme secretion in these cells, we have compared the characteristics of both these processes induced by either the receptor-directed agonist formylmethionyl-leucylphenylalanine (fMet-Leu-Phe) or the Ca2+-ionophore ionomycin. 2. The dependence on fMet-Leu-Phe concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(36 citation statements)
references
References 21 publications
5
31
0
Order By: Relevance
“…The number of receptors were 2.8 X 104/cell (A) and 1.3 X 104/cell (B), respectively. The affinity and the number of fMet-Leu-Phe receptors in this study are in the same range as those previously reported (17,27). This analysis revealed that the depressed receptor expression after reduction in the [Ca2+]i is most readily explained by a decreased number of fMet-Leu-Phe receptors on the cell surface.…”
Section: Resultssupporting
confidence: 90%
“…The number of receptors were 2.8 X 104/cell (A) and 1.3 X 104/cell (B), respectively. The affinity and the number of fMet-Leu-Phe receptors in this study are in the same range as those previously reported (17,27). This analysis revealed that the depressed receptor expression after reduction in the [Ca2+]i is most readily explained by a decreased number of fMet-Leu-Phe receptors on the cell surface.…”
Section: Resultssupporting
confidence: 90%
“…Recent investigations on stimulated lymphocytes (32), neutrophils (33), hepatocytes (34), and pancreas (35,36) have also demonstrated that removal of Ca2+ from the extracellular environment decreases the stimulation of PI metabolism and suggest (34) a distinction between changes in the availability of Ca2+ within the cell and the actual entry of Ca2+ through specific channels in the plasma membrane. Thus, the conclusions of several other studies support a model in which PI turnover is itself mediated by Ca2 .…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that the intracellular concentration of ionized Ca may play a crucial role in modulating the activity of PMN, for example, the stimulation of the cell by Ca2" ionophores (4)(5)(6)(7) and the inhibition of cell function by Ca2" antagonists (8-1 1). Intracellular Ca-binding proteins such as gelsolin and calmodulin seem to be implicated in the regulation of PMN movement and metabolism.…”
Section: Introductionmentioning
confidence: 99%